Financing African infrastructure: The role of China in African railways. (September 2021) - Marson, Marta; Maggi, Elena; Scacchi, Matteo
Abstract: In recent decades China has become an important source of official finance for African countries, especially for infrastructures. Most railways in Africa, built in the colonial period and then managed by state owned companies, experienced poor performances and deteriorated since independence. From the end of the last century, international financial institutions and traditional donors promoted private concessions in the railway sector, but results were generally below expectations. Based on project level data about official financial flows from the World Bank and from China, the study shows that China is now a main foreign finance provider for the railway systems in Africa. Through panel data regressions on flows at country leveland considering the determinants of funding, we find that financial allocation by China does not seem to be biased in favour of public or private management, nor to favour countries supported by the World Bank before the privatization phase. The needs of recipient countries seem to shape the allocation of funds by China, but also commercial interests play a role in this allocation. Overall funding from China seems to complement World Bank funding in the effort to fill the financing gap of the sector. Highlights: In the last decades China became a main donor for railway in Africa. China's allocation of funds is based on recipient countries' needs. China supports more the countries less supported by the World Bank. China doesn't favour countries supported by World Bank before privatization phase. Commercial interest of China plays a role in the allocation of its official funding.